Peningkatan Sumber Daya Manusia Di Sekolah Menengah Pertama Islam Bakti Asih Melalui Pemanfaatan Teknologi Informasi Dan Komunikasi - Dendy Bagaskara; Dety Mulyanti (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The use of information and communication technology (ICT) in education has become an important topic in optimizing human resources in schools. This article aims to provide an overview of the benefits and challenges of utilizing ICT in education, and how ICT can improve the quality of human resources in schools. The research method used in this article is a literature review conducted by studying references related to the use of ICT in education. The results and discussion show that the use of ICT in education can provide significant benefits, such as facilitating teachers in presenting teaching materials, providing access to more diverse information and learning materials, and improving interactions between teachers and students. However, there are challenges and barriers in utilizing ICT, such as accessibility problems to ICT infrastructure and difficulties in operating ICT devices. Therefore, efforts are needed to improve the accessibility and infrastructure of ICT in schools, as well as providing training and developing the competencies of teachers and students in operating ICT devices. In conclusion, this article presents useful information for the development of education in Indonesia, especially in terms of the utilization of ICT as a means to improve the quality of human resources in schools. With appropriate efforts, the use of ICT in education can provide more optimal and sustainable benefits for the improvement of human resources in schools.